The Agrobiodiversity Index - Remans, Roseline (2021)
The importance of monitoring agrobiodiversity as a key food system characteristic is increasingly recognised by farmers and consumers as well as by decision-makers and programme managers, particularly in the context of increasing climate change. Against this backdrop, the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT), together with multiple partners, developed the Agrobiodiversity Index. The Index is an innovative tool that, crossing disciplinary boundaries, brings together existing measures and data on breeding and seed systems, production systems, food markets and diets, analysing them under the lens of agricultural biodiversity for multiple goals.